Students Well-Being and Internet Use During the Pandemic - Claudia Chiorean (Babes-Bolyai University, 2023)
The study Internet Use and Students Well-being aimed to investigate the relationship between Internet addiction (generated by excessive Internet use = more than 6 hours/day outside of compulsory activities, more than 3 consecutive months) (Tao R. and all, 2010) and student well-being, depression, and social anxiety in pandemic times when digital consumer behavior has changed due to the specific context. The correlational design was applied in the research carried out on a group of 35 students from years 2 and 3 of the Faculty of Political, Administrative, and Communication Sciences, Babeș Bolyai University, Cluj through a series of scientifically validated tests: Psychological Scale Well, Berlin Social Support Scales, Internet Addiction Test, Self-Reported Stress Questionnaire (PSS), Liebowitz Social Anxiety Scale, DASS21. The results obtained showed positive correlations between the consumption of digital products and well-being (.494), with a statistical significance of 0.003, (≤0.05), and digital consumption and social anxiety (.319) with a statistical significance of 0.002. (≤0.05). In the case of the correlation between digital product consumption and depression, the correlation was negative (-0.228), with no statistical significance188 (≥0.05). Social support / positive relationships with others have proven to be a mediator between well-being and internet consumption. The overall effect of well-being on Internet addiction was positive (0.296), but statistically insignificant (0.708, not ≤0.05). Internet consumption for students who have pursued their academic pursuit digitally is a challenge to maintain the mental or physical well-being of the moment or perspective.